Treatment of Tricuspid Regurgitation With the FORMA Repair System - Perlman, Gidon Y.; Dvir, Danny (Frontiers in Cardiovascular Medicine, 2018)
Background: Tricuspid regurgitation (TR) is common and undertreated as the risk of surgery is high in this patient population. Transcatheter devices offer treatment with a lower procedural risk. The FORMA Tricuspid Valve Therapy system (Edwards Lifesciences) will be reviewed here. Device description: The system combines a spacer placed in the regurgitant orifice and a rail, over which the spacer is delivered, that is anchored to the endocardial surface of the RV. The spacer provides a surface for leaflet coaptation. Outcomes: 18 compassionate care patients and 29 patients included in the US EFS trial are reviewed. Patients were elderly (76 yrs) and high risk (Euroscore 2 was 9.0% and 8.1%, respectively). There were 2 procedural failures in both groups. Mortality at 30 days was 0% in the compassionate group and 7% in the EFS trial. TR was reduced in both groups; 2D/3D EROA 2.1 ± 1.8 cm2 to 1.1 ± 0.9 cm2 in the EFS trial and vena contracta width 12.1 ± 3.3mm to 7.1 ± 2.2mm. Symptomatic improvement was seen in both groups; the proportion of patients in NYHA class III/IV decreased from 84% to 28% at 30 days in the EFS group, and from 94% to 21% at 1 year, in the compassionate group. Conclusions Reduction of TR with FORMA system is feasible and sustained. Despite residual TR post procedure, the significant relative reduction in TR severity contributes to substantial clinical improvements in patients with a FORMA device in place.